﻿Simple and rapid LC-MS/MS method for determination of Piribedil in human plasma - Anas Alshishani; Inas Hasan; Fatima Ghanayem; Sewar Al-khasawneh; Alaa Abu Dayah (Pensoft Publishers, 2022)
A sensitive, simple, and fast LC-MS/MS method of analysis was developed and validated for the determination of piribedil in human plasma. Piribedil was extracted by protein precipitation using acetonitrile and separated on C18 Phenomenex Gemini column (150 × 4.6mm, 5 µm) using isocratic elution of 75% of ammonium acetate buffer (10 mM) and 25% acetonitrile at a flow rate of 1 ml.min-1 over 5 min run time. Piribedil and d8-Piribedil, as internal standard, were detected and quantified in positive ion mode via MRM at m/z 299/135 and 307/135 for piribedil and d8-piribedil, respectively. The suggested method for piribedil was validated according to FDA and EMA guidelines. The standard calibration curve was linear over the concentration range of 3.4-5952 pg.ml-1. The intra-day precision was 2.45-9.94% and accuracy 92.78-99.97%. The inter-day precision was 2.14-5.47% and accuracy 95.73-101.99%. The recovery of analyte and IS was 96.94% and 111.18%, respectively. piribedil in plasma was stable at benchtop (short term) for 24 h, in autosampler tray for 48 h, in instrumentation room for 24 h (post-preparative), after 5 freeze-thaw cycles (-70 °C), and 11 days in the freezer (-70 °C). The validated method was successfully applied to a bioequivalence study of piribedil formulations involving 15 healthy Jordanian volunteers.